The effectiveness of red ginger compress to prevent breast engorgement, reduce breast pain and prostaglandin hormone levels in postpartum mothers - Sari, Tatsa Putri Kumala; Wijayanti, Krisdiana; Anwar, M. Choiroel (Universitas Muhammadiyah Purwokerto, 2022)
Background: The active ingredients of ginger, such as gingerol, shogaol, zingerone, and paradol, are compounds that play a significant role in anti-inflammatory and analgesic properties. Previous studies that have been carried out using red ginger showed significant results on the severity of breast engorgement; however, these studies have not measured the decrease in levels of the hormone prostaglandin, which is an indicator of engorgement and pain. Previous studies have also shown the impracticality of the intervention. This study has made red ginger